PENGUJIAN ANALISA SARINGAN AGREGAT UNTUK PERENCANAAN CAMPURAN BETON MUTU NORMAL DENGAN METODE ANALITIS - Fitria, Winda (Jurnal Ilmiah Poli Rekayasa, 2024)
As one of the main fillers in concrete and asphalt mixtures, aggregate must comply with the required material standards. Aggregate sieve analysis is one of the tests that must be carried outbefore making a concrete Job Mix Formula (JMF). Aggregate sieve analysis testing is an important step to determine the size of the aggregate particle used in concrete mixtures and asphalt mixtures. Aggregate sieve analysis testing aims to analyze the aggregate grain size distribution, determine the maximum grain size of the aggregate used, ensure its conformity with technical specification standards and evaluate its impact on the quality and performance of construction materials. In this study, the combined percentage or percentage of coarse aggregate and fine aggregate was determined using analytical methods. This method involves using a series of sieves specific sizes to separate and measure the proportion of particles from the aggregate to be tested. Previous research shows that the distribution of aggregate gradations effect the stability, strength and durability of construction materials. The aggregate used as a test sample came from the Batang Kuranji river. The coarse aggregate used is 2000 grams in surface dry condition (SSD) and 1000 grams for fine aggregate. Dry surface condition on the aggregate were obtained after the aggregate was dried in an oven for 24 hours. The maximum aggregate size used for this test is 40 mm. Finenes Modulus (FM) of the material used as a test sample has accordance the required material fineness value. The results of the sieve analysis test provide a recommendation for a combined percentage of coarse aggregate of 64.8% and fine aggregate of 35.2%. Besides that, from the aggregate sive analysis test, it is known that the FM values obtained were 7.22 for coarse aggregate and 3.09 fine aggregate in the Batang Kuranji river.